Disfunção temporomandibular – validade da ressonância magnética e dos protocolos clínicos na avaliação da posição do disco articular - Maracci, Lucas Machado (2022)
Articular disc displacement is one of the main disorders that affect the temporomandibular joint (TMJ), whose diagnosis is performed by means of magnetic resonance imaging (MRI). Aiming at a broader scope of evaluation and diagnosis of this condition, diverse clinical protocols were proposed, but the scientific literature still presents divergences regarding the correlation of the findings of both exams. Thus, the present study aimed to carry out a systematic review to verify the accuracy of the diagnosis of disc displacement by means of clinical examination protocols compared with MRI, and considering examiners’ calibration. Appropriate combinations of terms were used according to each database (PubMed, Cochrane (Central), Scopus, Web of Science, LILACS, Embase and Science Direct; gray literature was searched through Google Scholar and DANS EASY Archive), without restriction of date or language. Also, the reference lists of studies selected for full-text reading were checked to identify possible articles not found. Two reviewers independently selected the studies according to eligibility criteria: observational diagnostic studies that evaluated TMJ disc displacement by means of MRI examination and clinical protocol. The Quality Assessment of Diagnostic Accuracy Studies (QUADAS-2) tool was used to assess the quality of the selected studies. The meta-analysis was conducted using the R Statistical software. Results are expressed through sensitivity and specificity, and their respective 95% confidence intervals and area under the curve (AUC). Of 55 studies selected for full reading, 20 were included in the systematic review and 17 in the meta-analysis. Of these, 3 were classified as low risk of bias, and the remaining 17 had one or more domains considered as high or uncertain risk of bias, according to the QUADAS-2 assessment. When compared to MRI, clinical protocols showed overall sensitivity and specificity for the diagnosis of disc displacement of 0.70 (0.58- 0.80) and 0.80 (0.66-0.89), respectively. For the diagnosis of DDWR, sensitivity was 0.64 (0.48-0.77) and specificity was 0.72 (0.48-0.87). For the diagnosis of DDWoR, the sensitivity was 0.57 (0.41-0.72) and the specificity was 0.93 (0.83-0.97). Only 8 studies reported on examiner calibration when performing clinical examination and/or MRI evaluation; nevertheless, calibration showed a tendency to improve disc displacement diagnosis. The sensitivity and specificity of clinical protocols in the diagnosis of disc displacement are below the recommended values, as well as the studies lack calibration of clinical and MRI examiners.